Thioredoxin Network in Plant Mitochondria: Cysteine S-Posttranslational Modifications and Stress Conditions - Martí, María Carmen; Jiménez, Ana; Sevilla, Francisca (Frontiers in Plant Science, 2020)
Plants are sessile organisms presenting different adaptation mechanisms that allow their survival under adverse situations. Among them, reactive oxygen and nitrogen species (ROS, RNS) and H2S are emerging as components not only of cell development and differentiation but of signaling pathways involved in the response to both biotic and abiotic attacks. The study of the posttranslational modifications (PTMs) of proteins produced by those signaling molecules is revealing a modulation on specific targets that are involved in many metabolic pathways in the different cell compartments. These modifications are able to translate the imbalance of the redox state caused by exposure to the stress situation in a cascade of responses that finally allow the plant to cope with the adverse condition. In this review we give a generalized vision of the production of ROS, RNS, and H2S in plant mitochondria. We focus on how the principal mitochondrial processes mainly the electron transport chain, the tricarboxylic acid cycle and photorespiration are affected by PTMs on cysteine residues that are produced by the previously mentioned signaling molecules in the respiratory organelle. These PTMs include S-oxidation, S-glutathionylation, S-nitrosation, and persulfidation under normal and stress conditions. We pay special attention to the mitochondrial Thioredoxin/Peroxiredoxin system in terms of its oxidation-reduction posttranslational targets and its response to environmental stress.